Determinan struktur modal dan pengaruhnya terhadap return saham pada industri barang dan konsumsi yang terdaftar di BEI - Wulandari, Ega Surya; Sunarko, Bambang; Tohir, Tohir (Performance, 2017)
Purpose: The purpose of this research is to examine influence between profitability measured by return on asset (ROA), liquidity measured by current ratio (CR), cash holding, non-debt tax shield, and asset growth on capital structure measured by debt to equity ratio (DER) and the influence on stock return. Methodology: This research was conducted during the period of 2011-2015. This research is quantitative research that used associative studies to determine the relationship or influence between two or more variables. Population in this research was all of consumer goods industries listed on Indonesia Stock Exchange during the period of research. This research combines multiple and simple regression analysis technique. In addition, hypothesis testing used coefficient of determination, F-test statistic, and t-test statistic. Findings: The result of this research indicates that profitability (ROA) has positive influence toward capital structure. Liquidity (current ratio) and cash holding have negative influence toward capital structure. Non-debt tax shield and asset growth do not have significant influence toward capital structure. Furthermore, capital structure does not have significant influence toward stock return. Keywords: profitability, liquidity, cash holding, non-debt-tax shield, asset growth, capital structure, stock return.